Black metal, trauma, subjectivity and sound : screaming the abyss - Shadrack, Jasmine Hazel (Emerald studies in metal music and culture., 2021)
This important book weaves together trauma, black metal theory and disability into a story of both pain and freedom. Drawing on her many years as a black metal guitarist, Jasmine Hazel Shadrack uses autoethnography to explore her own experiences of gender-based violence, misogyny and the healing power of performance.